Composite substrate and preparation method thereof
By using a magnesium-aluminum spinel single crystal wafer as a supporting substrate and surface-treating and bonding it with a piezoelectric substrate to form a composite substrate, the problem of difficult and high-cost processing of supporting substrate materials in the existing technology is solved, achieving It provides high-quality, low-cost substrate preparation and improves the performance and yield of SAW devices.
Patent Information
- Application Number
- CN202310888430.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The existing supporting substrate materials have problems such as difficult processing, high cost, poor quality consistency and poor processing performance, which affects the performance and yield of SAW devices.
A magnesium-aluminum spinel single crystal wafer is used as the supporting substrate, and is combined with the piezoelectric substrate through surface treatment and bonding technology to form a composite substrate. The PV value of the upper surface of the magnesia-aluminum spinel single crystal wafer is in the range of 2nm-30nm, and the average roughness Ra is in the range of 0.01nm-8nm. It is bonded by vacuum furnace pressure or normal temperature lamination.
It reduces the processing difficulty and cost of composite substrates, improves quality consistency and processing performance, and increases yield and productivity.
Smart Images

Figure CN119341495A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of surface acoustic wave devices, and in particular to a composite substrate and a preparation method thereof. Background Art
[0002] Surface acoustic wave (SAW) devices are widely used in communication equipment (such as mobile phones) to remove noise from signals. SAW devices are composed of a piezoelectric substrate and electrodes thereon. The principle is based on a piezoelectric crystal such as quartz, lithium niobate or lead titanate as a substrate. After the surface is polished, a metal film is evaporated on it. Two sets of cross-finger metal electrodes with energy conversion function are made through photolithography. Electrical signals are input to the metal electrodes, and the input signals are converted from electricity to sound to electricity, and finally output as electrical signals. Since the piezoelectric substrate material with piezoelectric effect generates a lot of heat during use, if this heat cannot be dissipated in time, the temperature rise will affect its piezoelectric performance and reduce the performance of the SAW device. Therefore, the piezoelectric substrate needs to be used in combination with a supporting substrate with good heat dissipation performance. Since the piezoelectric substrate is deformed due to the stress from the input electrical signal during use, the supporting substrate on which the piezoelectric substrate is installed must have excellent heat dissipation performance and high strength.
[0003] Among the existing support substrate materials, single crystals mainly include sapphire single crystals, but sapphire single crystals have high hardness, with a Mohs hardness of 9, and are difficult to process and relatively expensive, resulting in high processing and material costs. Polycrystalline materials mainly include polycrystalline materials such as aluminum oxide, magnesium oxide, silicon dioxide, silicon nitride, aluminum nitride, silicon carbide, and magnesium aluminum spinel, but support substrates made of polycrystalline materials have problems such as poor quality consistency, poor processing performance, and low yield and productivity. Summary of the invention
[0004] The purpose of this application is to provide a composite substrate and a preparation method thereof, which can reduce the processing difficulty of the composite substrate, reduce the processing cost and material cost of the composite substrate, improve the quality consistency and processing performance of the composite substrate, and improve the yield and production rate. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a composite substrate, which includes a piezoelectric substrate and a supporting substrate, wherein the supporting substrate is selected from a magnesium aluminum spinel single crystal wafer, the lower surface of the piezoelectric substrate is bonded to the upper surface of the supporting substrate, and the PV value of the upper surface of the magnesium aluminum spinel single crystal wafer is 2nm-30nm.
[0006] In one embodiment of the present application, the average roughness Ra of the upper surface of the magnesium aluminum spinel single crystal wafer is 0.01nm-8nm.
[0007] In one embodiment of the present application, the piezoelectric substrate is selected from a piezoelectric crystal wafer, and the piezoelectric crystal wafer is selected from at least one of a lithium tantalate wafer, a lithium niobate wafer, a lithium gallate wafer, a lithium germanate wafer and a titanium germanate wafer.
[0008] In one embodiment of the present application, the PV value of the lower surface of the piezoelectric crystal wafer is 2nm-30nm.
[0009] In one embodiment of the present application, the average roughness Ra of the lower surface of the piezoelectric crystal wafer is 0.01 nm-8 nm.
[0010] The second aspect of the present application provides a method for preparing the composite substrate provided in the first aspect of the present application, which comprises the following steps:
[0011] Cutting, contour processing, rough grinding, fine grinding and polishing the magnesium-aluminum spinel single crystal to obtain the magnesium-aluminum spinel single crystal wafer;
[0012] Polishing the piezoelectric crystal wafer to obtain a polished piezoelectric crystal wafer;
[0013] The upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the polished piezoelectric crystal wafer are surface treated, and then the upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the polished piezoelectric crystal wafer are bonded to obtain the composite substrate.
[0014] In one embodiment of the present application, the bonding is performed by a method of pressurizing the surfaces in a vacuum furnace or laminating the surfaces after activation at room temperature.
[0015] Beneficial effects of this application:
[0016] The present application provides a composite substrate and a preparation method thereof, wherein the composite substrate comprises a piezoelectric substrate and a supporting substrate, wherein the supporting substrate is selected from a magnesium aluminum spinel single crystal wafer, the lower surface of the piezoelectric substrate is bonded to the upper surface of the supporting substrate, and the PV value of the upper surface of the magnesium aluminum spinel single crystal wafer is 2nm-30nm. The preparation method of the composite substrate comprises: cutting, contour processing, rough grinding, fine grinding and polishing the magnesium aluminum spinel single crystal to obtain a magnesium aluminum spinel single crystal wafer; obtaining a polished piezoelectric crystal wafer; surface treating the upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the polished piezoelectric crystal wafer, and then bonding the upper surface of the magnesium aluminum spinel single crystal wafer to the lower surface of the polished piezoelectric crystal wafer to obtain a composite substrate. The composite substrate provided in the present application meets the above characteristics, can reduce the processing difficulty of the composite substrate, reduce the processing cost and material cost of the composite substrate, improve the quality consistency and processing performance of the composite substrate, and improve the yield and productivity.
[0017] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0019] Figure 1 This is a schematic diagram of the appearance of a composite substrate in one embodiment of the present application;
[0020] Figure 2 A schematic diagram of a piezoelectric crystal wafer in one embodiment of the present application;
[0021] Figure 3 A schematic diagram of a magnesium-aluminum spinel single crystal wafer in one embodiment of the present application;
[0022] Figure 4 This is a flow chart for preparing the composite substrate of Example 1. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0024] like Figure 1 As shown, the first aspect of the present application provides a composite substrate 100, which includes a piezoelectric substrate 2 and a supporting substrate 1, the supporting substrate 1 is selected from a magnesium aluminum spinel single crystal wafer, the lower surface of the piezoelectric substrate 2 is bonded to the upper surface of the supporting substrate 1, and the PV value of the upper surface of the magnesium aluminum spinel single crystal wafer is 2nm-30nm.
[0025] The inventors found that the hardness of magnesium aluminum spinel single crystal is moderate, with a Mohs hardness of 8. The processing difficulty and cost are lower than those of sapphire single crystal, and it is not easy to break. Compared with polycrystalline materials, it is easier to process because there are no grain boundaries, especially it is easier to obtain high surface accuracy and no defects caused by grain peeling. There is no unevenness in performance such as strength discreteness caused by uneven size and size distribution of polycrystalline grains. The support substrate prepared with magnesium aluminum spinel single crystal can meet the strength and heat dissipation requirements, and can achieve good bonding with the piezoelectric substrate through the van der Waals effect. Figure 3As shown, the PV value of the upper surface 4 of the magnesium-aluminum spinel single crystal wafer is 2nm-30nm. When the PV value of the upper surface of the magnesium-aluminum spinel single crystal wafer is within the range of this application, the bonding effect is better. In this application, the PV value refers to the difference between the highest point and the lowest point on the wafer surface.
[0026] Therefore, the supporting substrate in the present application is selected from a magnesium-aluminum spinel single crystal wafer, and when the PV value of the upper surface of the magnesium-aluminum spinel single crystal wafer is within the scope of the present application, it can reduce the processing difficulty of the composite substrate, reduce the processing cost and material cost of the composite substrate, improve the quality consistency and processing performance of the composite substrate, and improve the yield and productivity.
[0027] In one embodiment of the present application, the average roughness Ra of the upper surface of the magnesium-aluminum spinel single crystal wafer is 0.01 nm-8 nm. When the average roughness Ra of the upper surface of the magnesium-aluminum spinel single crystal wafer is within the range of the present application, the bonding effect is better.
[0028] In one embodiment of the present application, the piezoelectric substrate is selected from a piezoelectric crystal wafer, and the piezoelectric crystal wafer is selected from at least one of a lithium tantalate wafer, a lithium niobate wafer, a lithium gallate wafer, a lithium germanate wafer, and a titanium germanate wafer.
[0029] In one embodiment of the present application, Figure 2 As shown, the PV value of the lower surface 3 of the piezoelectric crystal wafer is 2nm-30nm. When the PV value of the lower surface of the piezoelectric crystal wafer is within the range of the present application, the smooth and flat surface is conducive to full contact between the lower surface of the piezoelectric crystal wafer and the upper surface of the magnesium aluminum spinel single crystal wafer, and the bonding effect is better.
[0030] In one embodiment of the present application, the average roughness Ra of the lower surface of the piezoelectric crystal wafer is 0.01 nm-8 nm. When the average roughness Ra of the lower surface of the piezoelectric crystal wafer is within the range of the present application, the bonding effect is better.
[0031] The second aspect of the present application provides a method for preparing the composite substrate provided in the first aspect of the present application, which comprises the following steps:
[0032] The magnesium-aluminum spinel single crystal is cut, contour processed, roughly ground, finely ground and polished to obtain a magnesium-aluminum spinel single crystal wafer;
[0033] Polishing the piezoelectric crystal wafer to obtain a polished piezoelectric crystal wafer;
[0034] The upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the polished piezoelectric crystal wafer are surface treated, and then the upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the polished piezoelectric crystal wafer are bonded to obtain a composite substrate.
[0035] In the present application, there is no particular limitation on the growth method of the magnesium-aluminum spinel single crystal, as long as the purpose of the present application can be achieved, such as any one of the flux method, flame melting method, vertical temperature gradient method, Czochralski method, crucible descent method and guided mold method. Preferably, it can be selected from the crucible descent method or the guided mold method.
[0036] In the present application, there is no particular restriction on the size of the magnesium-aluminum spinel single crystal wafer, as long as the purpose of the present application can be achieved, for example, the diameter of the magnesium-aluminum spinel single crystal wafer can be 50mm-150mm. In the present application, there is no particular restriction on the thickness of the magnesium-aluminum spinel single crystal wafer, as long as the purpose of the present application can be achieved, for example, the thickness of the magnesium-aluminum spinel single crystal wafer can be 0.3mm-0.5mm.
[0037] In the present application, there is no particular restriction on the size of the piezoelectric crystal wafer, as long as the purpose of the present application can be achieved, for example, the diameter of the piezoelectric crystal wafer can be 50mm-150mm. In the present application, there is no particular restriction on the thickness of the piezoelectric crystal wafer, as long as the purpose of the present application can be achieved, for example, the thickness of the piezoelectric crystal wafer can be 0.3mm-0.5mm.
[0038] The present application has no particular limitation on the polishing method, as long as the purpose of the present application can be achieved. For example, it can be selected from any one of mechanical polishing, chemical polishing and chemical mechanical polishing, or a combination thereof.
[0039] The present application has no particular restrictions on the method of regulating the PV value of the upper surface of the magnesium-aluminum spinel single crystal wafer, as long as the purpose of the present application can be achieved. For example, the PV value of the upper surface of the magnesium-aluminum spinel single crystal wafer can be regulated by regulating the polishing time. Within a certain time range, the PV value decreases when the polishing time is extended, and the PV value increases when the polishing time is shortened.
[0040] The present application has no particular restrictions on the method of regulating the average roughness Ra of the upper surface of the magnesium-aluminum spinel single crystal wafer, as long as the purpose of the present application can be achieved. For example, the average roughness Ra of the upper surface of the magnesium-aluminum spinel single crystal wafer can be regulated by regulating the polishing time. Within a certain time range, the average roughness Ra decreases when the polishing time is extended; the average roughness Ra increases when the polishing time is shortened.
[0041] The present application has no particular restrictions on the method of regulating the PV value of the lower surface of the piezoelectric crystal wafer, as long as the purpose of the present application can be achieved. For example, the PV value of the lower surface of the piezoelectric crystal wafer can be regulated by regulating the polishing time. Within a certain time range, the PV value decreases when the polishing time is extended, and the PV value increases when the polishing time is shortened.
[0042] The present application has no particular restrictions on the method of regulating the average roughness Ra of the lower surface of the piezoelectric crystal wafer, as long as the purpose of the present application can be achieved. For example, the average roughness Ra of the lower surface of the piezoelectric crystal wafer can be regulated by regulating the polishing time. Within a certain time range, the average roughness Ra decreases when the polishing time is extended; the average roughness Ra increases when the polishing time is shortened.
[0043] In the present application, surface treatment refers to surface treatment of the upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the piezoelectric crystal wafer, respectively. The present application does not particularly limit the surface treatment method, as long as the purpose of the present application can be achieved. For example, the surface treatment includes surface cleaning and drying. In the present application, ion activation is also performed after surface cleaning and drying. Ion activation increases surface activity and is more conducive to bonding.
[0044] In one embodiment of the present application, bonding is performed by pressurizing in a vacuum furnace or laminating the surfaces after activation at room temperature. In the present application, vacuum annealing is required after pressurizing in a vacuum furnace. When the above method is used for bonding, the bonding effect is better.
[0045] In the present application, the upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the piezoelectric crystal wafer are bonding surfaces.
[0046] The present application has no particular restrictions on the vacuum degree and pressure of the vacuum furnace, as long as the purpose of the present application can be achieved. For example, the vacuum degree of the vacuum furnace can be 10 -4 Pa-10 -2 Pa, the vacuum degree within the scope of this application can achieve better bonding effect and save time cost; the pressure applied to the wafer can be 0.1MPa-5MPa. This application has no special restrictions on the activation treatment method, as long as the purpose of this application can be achieved. For example, plasma activation treatment can be performed in a vacuum device.
[0047] In the present application, after the magnesium aluminum spinel single crystal wafer and the polished piezoelectric crystal wafer are bonded, the surface of one side of the bonded piezoelectric crystal wafer is ground and polished to thin the piezoelectric crystal wafer to 20μm-30μm, thereby obtaining a composite substrate.
[0048] Test method:
[0049] Test of PV value and average roughness Ra:
[0050] An atomic force microscope (model: Bruker Dimension Edge) was used to fix the sample on the scanning stage. The position and force of the probe were adjusted to make it contact with the sample surface. The scanning program was started, and the probe scanned the sample surface to obtain surface morphology information. The software processed and analyzed the scanned data to obtain the PV value and average roughness Ra.
[0051] Test of the number of bubbles after vacuum annealing:
[0052] The number of bubbles in the composite substrate after vacuum annealing was visually observed under a microscope (Olympus BX51M) at a magnification of 100-500 times.
[0053] Example 1
[0054] 1) Preparing 7 magnesium-aluminum spinel single crystal wafers: growing magnesium-aluminum spinel single crystals by a crucible descent method, cutting and processing the magnesium-aluminum spinel single crystals, and rough grinding, fine grinding and polishing to obtain 7 magnesium-aluminum spinel single crystal wafers with a diameter of 50 mm and a thickness of 0.3 mm; the PV value of the upper surface of the magnesium-aluminum spinel single crystal wafer and the average roughness Ra of the upper surface of the magnesium-aluminum spinel single crystal wafer are shown in Table 1;
[0055] 2) Preparing 7 lithium tantalate wafers: using a lithium tantalate wafer with a diameter of 50 mm and a thickness of 0.3 mm, polishing to obtain 7 polished lithium tantalate wafers; the PV value of the lower surface of the lithium tantalate wafer and the average roughness Ra of the lower surface of the lithium tantalate wafer are shown in Table 1;
[0056] 3) performing the following surface treatments on the polished upper surface of the magnesium aluminum spinel wafer and the lower surface of the lithium tantalate wafer respectively: cleaning, drying and plasma activation treatment, so that the two wafers are bonded together;
[0057] 4) The two wafers bonded together are pressurized in a vacuum furnace with a vacuum degree of 10 -3 Pa, the pressure is 0.1MPa, bonding is performed, followed by vacuum annealing;
[0058] 5) Grind and polish the surface of one side of the bonded lithium tantalate wafer, and thin the lithium tantalate wafer to 20 μm to obtain a composite substrate. The composite substrate preparation flow chart is as follows: Figure 4 shown.
[0059] Example 2
[0060] 1) Preparing 7 magnesium-aluminum spinel single crystal wafers: growing magnesium-aluminum spinel single crystals by a guided mold method, cutting and processing the magnesium-aluminum spinel single crystals, and performing rough grinding, fine grinding and polishing to obtain 7 magnesium-aluminum spinel single crystal wafers with a diameter of 50 mm and a thickness of 0.5 mm; the PV value of the upper surface of the magnesium-aluminum spinel single crystal wafer and the average roughness Ra of the upper surface of the magnesium-aluminum spinel single crystal wafer are shown in Table 1;
[0061] 2) Preparing 7 lithium niobate wafers: A lithium niobate wafer with a diameter of 50 mm and a thickness of 0.5 mm was polished to obtain 7 polished lithium niobate wafers; the PV value of the lower surface of the lithium niobate wafer and the average roughness Ra of the lower surface of the lithium niobate wafer are shown in Table 1; the upper surface of the magnesium aluminum spinel wafer and the lower surface of the lithium niobate wafer were cleaned, dried and plasma activated to bond the two wafers together;
[0062] 4) The two wafers bonded together are pressurized in a vacuum furnace with a vacuum degree of 10 -3 Pa, the pressure is 0.1MPa, bonding is performed, followed by vacuum annealing;
[0063] 5) Grinding and polishing the surface of one side of the bonded lithium niobate wafer to thin the lithium niobate wafer to 20 μm to obtain a composite substrate.
[0064] Comparative Example 1
[0065] 1) Preparing 7 magnesium-aluminum spinel polycrystalline wafers: cutting and processing the magnesium-aluminum spinel polycrystalline, rough grinding, fine grinding and polishing, to obtain 7 magnesium-aluminum spinel polycrystalline wafers with a diameter of 50 mm and a thickness of 0.5 mm; the PV value of the upper surface of the magnesium-aluminum spinel polycrystalline wafer and the average roughness Ra of the upper surface of the magnesium-aluminum spinel polycrystalline wafer are shown in Table 1;
[0066] 2) Preparing 7 lithium tantalate wafers: using a lithium tantalate wafer with a diameter of 50 mm and a thickness of 0.3 mm, polishing to obtain 7 polished lithium tantalate wafers; the PV value of the lower surface of the lithium tantalate wafer and the average roughness Ra of the lower surface of the lithium tantalate wafer are shown in Table 1;
[0067] 3) cleaning and drying the polished upper surface of the magnesium aluminum spinel polycrystalline wafer and the lower surface of the lithium tantalate wafer respectively, so as to bond the two wafers together;
[0068] 4) The two wafers bonded together are pressurized in a vacuum furnace with a vacuum degree of 10 -3 Pa, the pressure is 0.1MPa, bonding is performed, followed by vacuum annealing;
[0069] 5) Grinding and polishing the surface of one side of the bonded lithium tantalate wafer to thin the lithium tantalate wafer to 20 μm to obtain a composite substrate.
[0070] Comparative Example 2
[0071] 1) Preparing 7 magnesium-aluminum spinel polycrystalline wafers: cutting and processing the magnesium-aluminum spinel polycrystalline, rough grinding, fine grinding and polishing, to obtain 7 magnesium-aluminum spinel polycrystalline wafers with a diameter of 50 mm and a thickness of 0.5 mm; the PV value of the upper surface of the magnesium-aluminum spinel polycrystalline wafer and the average roughness Ra of the upper surface of the magnesium-aluminum spinel polycrystalline wafer are shown in Table 1;
[0072] 2) Preparing 7 lithium niobate wafers: polishing a lithium niobate wafer with a diameter of 50 mm and a thickness of 0.5 mm to obtain 7 polished lithium niobate wafers; the PV value of the lower surface of the lithium niobate wafer and the average roughness Ra of the lower surface of the lithium niobate wafer are shown in Table 1;
[0073] 3) cleaning and drying the polished upper surface of the magnesium aluminum spinel polycrystalline wafer and the lower surface of the lithium niobate wafer respectively, so as to bond the two wafers together;
[0074] 4) The two wafers bonded together are pressurized in a vacuum furnace with a vacuum degree of 10 -3 Pa, the pressure is 0.1MPa, bonding is performed, followed by vacuum annealing;
[0075] 5) Grinding and polishing the surface of one side of the bonded lithium niobate wafer to thin the lithium niobate wafer to 20 μm to obtain a composite substrate.
[0076] The preparation parameters and processing conditions of the composite substrates of various embodiments and comparative examples are shown in Table 1.
[0077] Table 1
[0078]
[0079] Note: In Table 1, “ / ” indicates that the material was not transferred to the next process due to cracking during the polishing process / cloudiness and impurities inside the material after polishing and could not be used.
[0080] Referring to Table 1, it can be seen from Examples 1 and 2 that a magnesium aluminum spinel single crystal wafer is used as a supporting substrate, the lower surface of the piezoelectric crystal wafer is bonded to the upper surface of the magnesium aluminum spinel single crystal wafer, and the PV value of the upper surface of the magnesium aluminum spinel single crystal wafer is within the scope of the present application. After vacuum annealing of the composite substrate obtained by the preparation method of the present application, the number of bubbles in the 7 pieces in Example 1 is 0, and the yield is 100%. The number of bubbles in 6 of the 7 pieces in Example 2 is 0, and the yield is 85.7%. This shows that the present application uses a magnesium aluminum spinel single crystal wafer as a supporting substrate, and the PV value of the upper surface of the magnesium aluminum spinel single crystal wafer is within the scope of the present application, which can reduce the processing difficulty of the composite substrate, reduce the processing cost and material cost of the composite substrate, improve the quality consistency and processing performance of the composite substrate, and improve the yield and productivity.
[0081] The average roughness Ra of the upper surface of the magnesium-aluminum spinel single crystal wafer usually affects the bonding effect. It can be seen from Example 1 and Example 2 that when the average roughness Ra of the upper surface of the magnesium-aluminum spinel single crystal wafer is within the scope of this application, the number of bubbles in the obtained composite substrate after vacuum annealing is 0, and the yield is high, which indicates that the composite substrate has a good bonding effect.
[0082] The PV value of the lower surface of the piezoelectric crystal wafer usually affects the bonding effect. It can be seen from Examples 1 and 2 that when the PV value of the lower surface of the piezoelectric crystal wafer is within the range of the present application, the number of bubbles in the obtained composite substrate after vacuum annealing is 0, and the yield is high, which indicates that the composite substrate has a good bonding effect.
[0083] The average roughness Ra of the lower surface of the piezoelectric crystal wafer usually affects the bonding effect. It can be seen from Examples 1 and 2 that when the average roughness Ra of the lower surface of the piezoelectric crystal wafer is within the range of this application, the number of bubbles in the obtained composite substrate after vacuum annealing is 0, and the yield is high, which indicates that the composite substrate has a good bonding effect.
[0084] Referring to Table 1, it can be seen from Comparative Examples 1 and 2 that when the magnesium-aluminum spinel polycrystalline wafer is used as the supporting substrate, 1 piece and 2 pieces respectively cracked / had impurities and fog during the polishing process and could not be used. After the remaining 6 pieces and 5 pieces were bonded to obtain the composite substrate, the number of bubbles was 0 in 4 pieces and 3 pieces respectively, and the yields were 57.1% and 42.9% respectively, indicating that the composite substrates obtained by using the magnesium-aluminum spinel polycrystalline wafer as the supporting substrate have poor processing performance, low yield and high processing cost.
[0085] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.
Claims
1. A composite substrate, comprising a piezoelectric substrate and a supporting substrate, wherein the supporting substrate is selected from a magnesium-aluminum spinel single crystal wafer, the lower surface of the piezoelectric substrate is bonded to the upper surface of the supporting substrate, and the PV value of the upper surface of the magnesium-aluminum spinel single crystal wafer is 2nm-30nm.
2. The composite substrate according to claim 1, wherein: The average roughness Ra of the upper surface of the magnesium aluminum spinel single crystal wafer is 0.01nm-8nm.
3. The composite substrate according to claim 1, wherein: The piezoelectric substrate is selected from piezoelectric crystal wafers, and the piezoelectric crystal wafer is selected from at least one of lithium tantalate wafers, lithium niobate wafers, lithium gallate wafers, lithium germanate wafers and titanium germanate wafers.
4. The composite substrate according to claim 3, wherein: The PV value of the lower surface of the piezoelectric crystal wafer is 2nm-30nm.
5. The composite substrate according to claim 3, wherein: The average roughness Ra of the lower surface of the piezoelectric crystal wafer is 0.01nm-8nm.
6. A method for preparing a composite substrate according to any one of claims 1 to 5, comprising the following steps: Cutting, contour processing, rough grinding, fine grinding and polishing the magnesium-aluminum spinel single crystal to obtain the magnesium-aluminum spinel single crystal wafer; Polishing the piezoelectric crystal wafer to obtain a polished piezoelectric crystal wafer; The upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the polished piezoelectric crystal wafer are surface treated, and then the upper surface of the magnesium aluminum spinel single crystal wafer and the lower surface of the polished piezoelectric crystal wafer are bonded to obtain the composite substrate.
7. The preparation method according to claim 6, wherein: The bonding is performed by a method of applying pressure in a vacuum furnace or laminating the surfaces after activation at room temperature.